2013
DOI: 10.2166/wst.2013.052
|View full text |Cite
|
Sign up to set email alerts
|

The survival of mycobacteria in pure human urine

Abstract: Mycobacterial pathogens can be excreted in human urine by some infected individuals. High numbers of pathogenic mycobacteria in the urine could represent a new transmission route for mycobacterial infections if the urine is used for crop fertilization. In this study, the survival of spiked Mycobacterium aurum and M. fortuitum as fast-growing mycobacteria and M. avium and M. bovis as slow-growing mycobacteria were tested in urine. The tests were conducted in fresh (<1 day old) and stored human urine (>6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 254 publications
1
4
0
Order By: Relevance
“…Each of these factors significantly impacted the community structure, with urine age and pH being the major drivers of the bacterial community structure (Figure b; Table SI-2). This finding is consistent with previous research that found a positive correlation between pH and ammonia concentrations with the removal of certain bacteria. ,, …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Each of these factors significantly impacted the community structure, with urine age and pH being the major drivers of the bacterial community structure (Figure b; Table SI-2). This finding is consistent with previous research that found a positive correlation between pH and ammonia concentrations with the removal of certain bacteria. ,, …”
Section: Resultssupporting
confidence: 93%
“…This finding is consistent with previous research that found a positive correlation between pH and ammonia concentrations with the removal of certain bacteria. 7,11,37 Adonis analysis confirmed that significant differences existed in the bacterial communities between urine classified as young, hydrolyzed <80 days, and hydrolyzed >80 days (p-value = 0.001). From the time when urine was over 80 days old, there was little or no statistical difference in community composition among samples (p-value > 0.05).…”
Section: ■ Materials and Methodsmentioning
confidence: 83%
“…Urine from infected humans may also contaminate the environment and be a source of Mtb. Studies have shown that pathogenic mycobacteria in fresh human urine could survive up to 2 weeks at 30°C and up to 6 weeks at 15°C (44). Inadequate treatment of waste water may also be a potential source, as Mtb was found in stream water in Slovakia (45).…”
Section: Discussionmentioning
confidence: 99%
“…Most mycobacterial pathogens, causing tuberculosis and tuberculosis-like infections in other soft tissues or lymph nodes, are excreted via human urine if the infection is in kidneys or stool for GITB infections [53][54][55][56][57]. The detection of TB through human stool analysis has also been reported [58].…”
Section: Mycobacterium Tuberculosis Complex In Excretamentioning
confidence: 99%
“…The survival times of M. bovis and M. tuberculosis in human urine has been reported to be over 10 days at 4 °C and below 3 days at 22 °C [148]. In contrast, at 15 o C, mycobacteria have been reported to survive up to 6 weeks [54]. According to Scanlon and Quinn [147], the survival time of M. tuberculosis in sterilized manure kept at room temperature was up to 172 days.…”
Section: Survival Of Mtbc In Excreta and Wastewatermentioning
confidence: 99%